Membangun Literasi Keuangan Melalui Pembiasaan Menabung Pada Siswa Sekolah Dasar - Adriani A; Sinta Oktavia Wulandari; Muhammad Haikal Mukti (Yayasan Daarul Huda Kruengmane, 2026)
Financial literacy is an important competency that should be instilled from elementary school age so that children develop the ability to manage money wisely. Limited understanding of financial management means that many children have not yet developed saving habits and still tend to use their pocket money consumptively. This study aims to analyze the effectiveness of a financial literacy education program through saving habits among elementary school students. The community service activity was conducted using a lecture method on the importance of saving, followed by a practical activity in which students decorated piggy banks as saving containers. Rewards were given to children whose piggy banks had the most creative decorations. The results showed that the children were highly enthusiastic and responded positively by actively listening to the explanations and competing to decorate their piggy banks creatively. This activity is expected to foster a more frugal mindset among children, encourage them to use the pocket money provided by their parents wisely, and develop a consistent habit of saving.